2008
DOI: 10.1080/02643290802309514
|View full text |Cite
|
Sign up to set email alerts
|

Different letter-processing strategies in diagnostic subgroups of developmental dyslexia

Abstract: Normally reading adults (N = 15) and primary school children (N = 24) and two diagnostic subgroups of children with developmental dyslexia (N = 21)-all native German speakers-performed a successive same-different task with pairs of letters and nonletters (pseudoletters or geometrical shapes). The first item of a pair was always presented on its own, and the second either on its own or surrounded by a congruent or incongruent nontarget shape. Adults showed congruence effects with nonletters but not with letters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 52 publications
2
50
0
Order By: Relevance
“…On the one hand, only children with multiple deficits might develop manifest literacy impairments leading to developmental dyslexia (Bishop, 2006;Snowling, 2008). On the other hand, there might be diagnostic subgroups of dyslexic individuals that are characterized by different core deficits (Aaron et al, 1999;Heim et al, 2008;Lachmann et al, 2005;Lachmann & van Leeuwen, 2008). Interesting enough, a subject by subject analysis of the data revealed that 65% of our dyslexic sample showed a significant deficit in vowel length discrimination in the temporal conditions.…”
Section: Discussionmentioning
confidence: 83%
“…On the one hand, only children with multiple deficits might develop manifest literacy impairments leading to developmental dyslexia (Bishop, 2006;Snowling, 2008). On the other hand, there might be diagnostic subgroups of dyslexic individuals that are characterized by different core deficits (Aaron et al, 1999;Heim et al, 2008;Lachmann et al, 2005;Lachmann & van Leeuwen, 2008). Interesting enough, a subject by subject analysis of the data revealed that 65% of our dyslexic sample showed a significant deficit in vowel length discrimination in the temporal conditions.…”
Section: Discussionmentioning
confidence: 83%
“…But the automatization deficit approach cannot explain a number of effects (Rusiak et al, 2007), as for instance the ones observed in another set of experiments using stimuli such as those displayed in Figure 3 (Lachmann and van Leeuwen, 2004, 2008b; van Leeuwen and Lachmann, 2004; see also Fernandes et al, 2014). Similarly to Eriksson’s classical Flanker study (Eriksen and Eriksen, 1974), we investigated effects of congruence of the surrounding context on the processing of the central target.…”
Section: Analytic Processing Of Letters In Experimental Studiesmentioning
confidence: 97%
“…Lachmann & van Leeuwen, 2008). As discussed above, a consistent print-to-sound mapping is very helpful in this regard and is the reason why Italian children, for instance, learn to recode letter strings with 90% accuracy within a few months (Goswami et al, 1997;Seymour et al, 2003) in contrast to children learning to read English, who acquire the same level of accuracy only after 3-4 years of reading instruction (Goswami et al, 1997).…”
Section: Reading Level Control Groupsmentioning
confidence: 97%
“…Lachmann, Khera, Srinivasan, & van Leeuwen, 2012;Lachmann & van Leeuwen, 2008). Note that the visual routines supporting object recognition that humans have acquired during evolution can actually impede reading acquisition.…”
Section: Mirror Invariancementioning
confidence: 99%